2007
DOI: 10.1243/09544054jem847
|View full text |Cite
|
Sign up to set email alerts
|

Turning of hardened AISI 4340 steel using coated carbide inserts

Abstract: The machining of hardened steels employing polycrystalline cubic boron nitride and ceramic tooling has been comprehensively investigated over the last 20 years; however, the development of newer cemented carbide grades has extended the use of this group of materials to the machining of steels hardened up to 45 HRC (Rockwell C). The current paper is therefore concerned with continuous turning of AISI 4340 steel hardened from 250 to 525 HV using coated carbide tools in order to investigate whether this cutting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 16 publications
0
34
0
Order By: Relevance
“…However, harder workpiece employs higher cutting forces and generates higher cutting temperatures [1][2][3][4], which have a strong influence on the tool wear rate through different tool wear mechanisms like abrasion, adhesion, and diffusion. The tool wear, especially the flank wear, which adversely affects the dimensional accuracy and product quality, is the main hurdle in the wide implementation of coated carbide tools to machining of hardened steel in the industry.…”
Section: Introductionmentioning
confidence: 99%
“…However, harder workpiece employs higher cutting forces and generates higher cutting temperatures [1][2][3][4], which have a strong influence on the tool wear rate through different tool wear mechanisms like abrasion, adhesion, and diffusion. The tool wear, especially the flank wear, which adversely affects the dimensional accuracy and product quality, is the main hurdle in the wide implementation of coated carbide tools to machining of hardened steel in the industry.…”
Section: Introductionmentioning
confidence: 99%
“…de Lima et al [18] performed turning operation of AISI 4340 steel hardened from 250 to 525 HV using coated carbide tools to investigate its potentials of applications in hard turning. It is observed that, the machining force component increases with the work material hardness.…”
Section: Introductionmentioning
confidence: 99%
“…However, high performance of the TiAIN coated tool regarding wear resistance and surface finish. To investigate potentials of applications in hard turning, (Lima et al 2007) have carried out turning operations using coated carbide tools on AISI 4340 steel hardened from 250 to 525 HV. It was concluded that, the cutting force increases with the work material hardness.…”
Section: Introductionmentioning
confidence: 99%